2009
DOI: 10.1016/j.landusepol.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Recreational demand for farm commonage in Ireland: A contingent valuation assessment

Abstract: This paper measures willingness to pay (WTP) for public access and trail improvements on commonage farmland for recreational walking in upland and lowland areas of Connemara region in the West of Ireland using the Contingent Valuation Method (CVM).Common to both upland and lowland commonage sites was the much higher ranking for infrastructural features by those WTP for scenario implementation compared to those preferring the status quo. Results for those expressing a positive WTP reveal a median willingness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…The second section dealt with monetary valuation. "Prior to the CVM questions, respondents were presented with the valuation scenario (formulated to be as realistic as possible) and reminded of the main assets of the periurban space (Kotchen and Reiling, 2000;Pedroso et al, 2007;Buckley et al, 2009). The selection of this scenario was intended to improve the credibility of the proposal and to minimise the risks of misunderstanding inherent in this valuation method" In view of the evidence presented by certain authors as to the role of socioeconomic and demographic factors in monetary valuation, the third group of questions elicited personal data such as age, gender, education level and income.…”
Section: Questionnaire Design and Data Collectionmentioning
confidence: 99%
“…The second section dealt with monetary valuation. "Prior to the CVM questions, respondents were presented with the valuation scenario (formulated to be as realistic as possible) and reminded of the main assets of the periurban space (Kotchen and Reiling, 2000;Pedroso et al, 2007;Buckley et al, 2009). The selection of this scenario was intended to improve the credibility of the proposal and to minimise the risks of misunderstanding inherent in this valuation method" In view of the evidence presented by certain authors as to the role of socioeconomic and demographic factors in monetary valuation, the third group of questions elicited personal data such as age, gender, education level and income.…”
Section: Questionnaire Design and Data Collectionmentioning
confidence: 99%
“…However, this requires the replacement of an existing land-use. Traditionally, afforestation would occur on sub-marginal land but this is increasingly valued for biodiversity and recreation (Buckley et al, 2009;Bullock et al, 2012), which may be impacted negatively by afforestation (Buscardo et al, 2008). Such areas are therefore becoming less available for land conversion in general, including for afforestation.…”
Section: Discussionmentioning
confidence: 99%
“…Those respondents who indicated that their participation was dependant on financial compensation were then presented with a contingent valuation WTA scenario to establish the minimum amount a landowner would be prepared to accept (D/per annum) per metre of walkway crossing their land to ensure participation. Using data from a pilot survey WTA bids of 10 cent, 25 cent, 50 cent, D1 and D3 (per metre per annum) were chosen, assigned equally and randomly among landowners seeking compensation (for a more detailed discussion of this WTA analysis the reader is referred to Buckley et al, 2009a).…”
Section: Data Collection -Farmers Willingness To Acceptmentioning
confidence: 99%
“…This is a serious constraint on tourism development especially in rural areas where it is now widely recognised that rural based recreational activities have the potential to deliver significant economic benefits through tourism based revenue and as such can be an important tool for rural and regional development (Moore and Barthlow, 1998;Lane, 1999;Vaughan et al, 2000;FailteIreland, 2005). A variety of issues such as potential interference with agricultural activities, insurance liability and potential invasion of privacy have been reported by landowners as reasons why they may be unwilling to allow public access to their farmland for walking related activities (Mulder et al, 2006;Buckley et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%